HNTs/GO composite as efﬁcient catalyst for ring-opening polymerization of ε-Caprolactone. Issue 9 (13th June 2019) - Ma, Rui; Hu, Pan; Fan, Jinxu; Tang, Wei; Chen, Tao; Shi, Luyao
ABSTRACT: Polycaprolactone (PCL) has been widely applied based on the biocompatibility and biodegradability. It is important to investigate the safe and efficient catalyst system for ring-opening polymerization of monomer ε-caprolactone (ε-CL). In our work, Halloysite/Graphene Oxide (HNTs/GO) composite is successfully prepared by electrostatic self-assembly and used as an effective catalyst for the ring-opening polymerization of ε-CL. The structures, morphologies and thermal properties of the products are subsequently characterized. The results show that the synthesized PCL are semi-crystalline and observed to be lamellar, which depend on the template effects of HNTs/GO composite. The HNTs/GO composite serves as an effective catalyst and a reinforcing filler simultaneously to improve the thermal stability of the prepared PCL. Graphical Abstract: